Evaluating the hydrological resilience of estuarine wetlands in the Western Cape using environmental tracers: an inter-catchment comparison - Welham, Angela Ruth (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2024.